THE RELATIONSHIP BETWEEN TEACHERS’ MOTIVATION AND STUDENTS’ ENGLISH COMMUNICATION SKILL - Widya Adhariyanty Rahayu; Adriani Kala’lembang (INOVISH JOURNAL, 2021)
Motivation plays an essential role in the teaching and learning process of students in class. Through motivation can be determined success or failure in the teaching and learning process. This study was conducted to determine the relationship of teacher motivation with students' English communication skills in Middle School of Malang Regency. Calculation of the correlation between motivation and English communication skills of students using Stastical Product and Service Solution V.23 (SPSS 23). In descriptive statistics with 30 respondents, the average motivation value was 44.67 with a standard deviation of 3.14. While the average value for English communication skills or student achievement is 30 people at 78.90 with a standard deviation of 3.99. The correlation between the two variables of motivation and achievement is 0.741. In sig. (2-tailed) of 0,000 in the sense that there is a significant correlation between students' motivation and English communication skills (achievement) because the correlation value is smaller than 0.05.